The 2001 CDC Recommendations for Using Fluoride to Prevent and Control Dental Caries in the United States - Herschel S. Horowitz, DDS, MPH (Blackwell Synergy)
The Centers for Disease Control and Prevention (CDC) published ÃƒÂ¢Ã¢â€šÂ¬Ã‚ÂRecommenda tions for Using Fluoride to Prevent and Control Dental Caries in the United StatesÃƒÂ¢Ã¢â€šÂ¬Ã‚Â in August 2001 (1). At its 2002 annual meeting in San Diego, the Section on Community and Preventive Dentistry of the American Dental Education Association sponsored a session, ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œNew Fluoride Recommendations: Is There Adequate Evidence?ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â At that session, I was asked to analyze the evidence for and against the recommendations following an overview of them by Dr. Scott Presson of CDC. My presentation was excerpted from the commentary that follows.